PENERAPAN REDUNDANCY FIREWALL PFSENSE MENGGUNAKAN METODE CARP DENGAN PFSYNC DAN XMLRPC SYNC - Muhammad Syahrul Fattah Ramadhan; Nendi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
The use of information technology (IT) has grown rapidly in various sectors, such as business, industry, education, healthcare, and government. With the increasing dependence on IT, it is important for organizations to ensure high availability of the firewall system. When the firewall experiences problems or is unavailable, computer networks can be vulnerable to cyber attacks such as DoS (Denial of Service), Port Scanning, and others, resulting in financial loss, reputation damage, and loss of customer trust. On the other hand, high availability of the firewall system can help organizations meet regulatory requirements, maintain customer trust, and improve operational efficiency. The method used in this research is the Network Development Life Cycle (NDLC), which consists of six stages: Analysis, Design, Simulation Prototyping, Implementation, Monitoring, and Management. From the test results, it can be concluded that after testing 10 times with the CARP method, sending 30 packets and then the master node dies, this method has an average of 27.2 packets received, downtime of around 2.8 seconds, and packet loss of around 9.2%. These results make the CARP method have high availability against system or network failures.